Pembangunan pertanian di Desa Wonocoyo, Kecamatan Panggul, Kabupaten Trenggalek - Tanjung, Ahmad Hartono; Muhammad, Faqih Fawwaz; Talitha, Firzanah Adya; Aditama, Muri; Asna, Zaki Millati; Antriyandarti, Ernoiz (Journal of Critical Ecology, 2024)
Abstract